1998
DOI: 10.2307/3433987
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Signaling through Regulation of Protein Tyrosine Phosphorylation in Endothelial Cells

Abstract: Tyrosine phosphorylation of proteins, controlled by tyrosine kinases and protein tyrosine phosphatases, plays a key role in cellular growth and differentiating. A wide variety of hormones, growth factors, and cytokines modulate cellular tyrosine phosphorylation to transmit signals across the plasma membrane to the nucleus. Recent studies suggest that reactive oxygen species (ROS) also induce cellular protein tyrosine phosphorylation through receptor or nonreceptor tyrosine kinases. To determine whether protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…Since tyrosine phosphorylation has been shown to be an important event in Raf-1 activation (6, 7), and because one mechanism by which reactive oxygen species has been reported to modulate signal transduction pathway is via alteration in protein tyrosine phosphorylation (26,45), several tyrosine kinase inhibitors were tested to determine their relative effects on Raf-1 kinase activation by the combination of PMA and H 2 O 2 . In these studies v-Ha-ras-transformed cells were used because these cells were found to be more susceptible to PMA and H 2 O 2 activation than parental NIH 3T3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Since tyrosine phosphorylation has been shown to be an important event in Raf-1 activation (6, 7), and because one mechanism by which reactive oxygen species has been reported to modulate signal transduction pathway is via alteration in protein tyrosine phosphorylation (26,45), several tyrosine kinase inhibitors were tested to determine their relative effects on Raf-1 kinase activation by the combination of PMA and H 2 O 2 . In these studies v-Ha-ras-transformed cells were used because these cells were found to be more susceptible to PMA and H 2 O 2 activation than parental NIH 3T3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanism underlying junctional protein phosphorylation is undetermined. Oxidant-dependent intracellular phosphorylation events are important in growth factor receptor activation and epithelial barrier function, 22,[34][35][36] but few studies have examined the response of individual junctional components to cytokine-induced oxidant activation. Our findings suggest that phosphorylation of VE-cadherin, the predominant component of endothelial adherens junctions, [37][38][39][40] proceeds through the production of endogenous oxidants.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 has been reported to stimulate multiple forms of vascular phospholipases (PLs), including PLA 2 , PLC, and PLD, 87,88 and ROS and RNS modulate the activity of arachidonic acid-metabolizing enzymes and directly modify lipids to species that are vasoactive. The signaling pathways through which ROS control the activity of PLs are rather poorly understood.…”
Section: Eicosanoids and Plsmentioning
confidence: 99%